2002
DOI: 10.1523/jneurosci.22-09-03376.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-Jun N-Terminal Kinase and p38 in an Alzheimer's Disease Model Is Associated with Amyloid Deposition

Abstract: The mechanisms by which neurons and synapses are lost in Alzheimer's disease (AD) are not completely understood. To characterize potential signaling events linked to AD pathogenesis, activation-specific antibodies were used to examine mitogen-activated protein kinase (MAPK) kinase pathways at various ages in mice transgenic for human amyloid precursor protein-695 with the Swedish familial AD mutations (Tg2576) and homozygous for a P264L familial AD mutation introduced by targeting of the presenilin-1 gene (PS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
190
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(204 citation statements)
references
References 60 publications
13
190
1
Order By: Relevance
“…These mice showed some similarities with the Tg2576 + PS1P264L double transgenic mouse model of Savage et al (2002) as both AD models showed increased JNK pathway activation, a feature displayed by the human AD brain (Zhu et al, 2001;Savage et al, 2002). These results support the known strong correlation between hCTF99 or its products and increased JNK pathway activation in the pathogenesis of AD.…”
Section: Neuropathological Features Of Tg-bctf99/b6 As An Ad Modelsupporting
confidence: 69%
See 1 more Smart Citation
“…These mice showed some similarities with the Tg2576 + PS1P264L double transgenic mouse model of Savage et al (2002) as both AD models showed increased JNK pathway activation, a feature displayed by the human AD brain (Zhu et al, 2001;Savage et al, 2002). These results support the known strong correlation between hCTF99 or its products and increased JNK pathway activation in the pathogenesis of AD.…”
Section: Neuropathological Features Of Tg-bctf99/b6 As An Ad Modelsupporting
confidence: 69%
“…brain shows phospho-JNK up-regulation (Zhu et al, 2001;Savage et al, 2002) prompted us to examine the levels of phospho-JNK, -ERK, -p38 MAPKs, and phospho-c-Jun in the Tg-hCTF99/B6 brain. It was found that the levels of phospho-JNK and phospho-c-Jun in the whole cerebrum homogenate of Tg-hCTF99/B6 at 15 months were notably higher than those of age-matched controls, whereas the expressions of JNK1, JNK2, JNK3, phospho-ERK, and phospho-p38 were not significantly changed (Fig.…”
Section: Expression Of Cell-death-related Proteins In the Tg-bctf99/bmentioning
confidence: 99%
“…Another pro-apoptotic signaling cascade induced by ER stress is the activation of JNK/c-Jun, which is attenuated by Herp. Since activation of these cascades is involved in A␤-induced neurotoxicity (10,27,49), Herp may protect cells exposed to A␤ by suppressing caspase 12 and JNK activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both p38 MAPK and its upstream kinase MKK6 are activated in AD brain tissue as demonstrated by immunohistochemistry (17,18). Activation of the p38 MAPK signaling is also reported in an AD-relevant animal model (19). Moreover, a previous report demonstrated that A␤ employs synaptic depression to drive endocytosis of synaptic AMPA receptor by activating p38 MAPK (20).…”
mentioning
confidence: 88%